NILAI SOSIAL TRADISI RITUAL KEAGAMAAN RATIB RAMBAI PADA MASYARAKAT KUBU KABUPATEN ROKAN HILIR - Afna Fitria Sari (Abrahamic Religions: Jurnal Studi Agama-Agama, 2021)
Ritual Ratib Rambai a hereditary tradition for appealing welfare and prevent a bad fortune which still continues till this day that contains a worth social value. It makes close to Allah SWT, has a good kinship, solidarity with others and they proud to have the culture. This research aims to find out the social values from Ritual Ratib Rambai for Kubu community Rokan Hilir Region, Riau Province. The study executes by qualitative method and descriptive view, that doesn’t use grades as a method but using information from community experiences to find out the social values which contained from Ritual Ratib Rambai and confirmed by continuous literacy. This study also explained the history and implementation of Ritual ratib rambai that exist in Kubu community.